2020
DOI: 10.1093/gigascience/giaa120
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive venom evolution and toxicity in octopods is driven by extensive novel gene formation, expansion, and loss

Abstract: Background Cephalopods represent a rich system for investigating the genetic basis underlying organismal novelties. This diverse group of specialized predators has evolved many adaptations including proteinaceous venom. Of particular interest is the blue-ringed octopus genus (Hapalochlaena), which are the only octopods known to store large quantities of the potent neurotoxin, tetrodotoxin, within their tissues and venom gland. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 119 publications
1
22
0
Order By: Relevance
“…This could also suggest that the position of the replacement is more important than the amino acid change per se. Our results are also congruent with previous findings for Hapalochlaena lunulata (Geffeney et al, 2019) and Hapalochlaena maculosa (Whitelaw et al, 2020), as NaV1.4a Domain I is highly conserved in both octopod species. Furthermore, unlike the pufferfishes A. nigropunctatus and T. nigroviridis (Jost et al, 2008), the garter snake Thamnophis couchii (Feldman et al, 2012) and the octopuses Hapalochlaena lunulata (Geffeney et al, 2019) and Hapalochlaena maculosa (Whitelaw et al, 2020), replacements were also not observed in the NaV1.4a Domain III of L. sceleratus.…”
Section: Ttx Resistance Of Scna4 Sodium Channelsupporting
confidence: 93%
See 1 more Smart Citation
“…This could also suggest that the position of the replacement is more important than the amino acid change per se. Our results are also congruent with previous findings for Hapalochlaena lunulata (Geffeney et al, 2019) and Hapalochlaena maculosa (Whitelaw et al, 2020), as NaV1.4a Domain I is highly conserved in both octopod species. Furthermore, unlike the pufferfishes A. nigropunctatus and T. nigroviridis (Jost et al, 2008), the garter snake Thamnophis couchii (Feldman et al, 2012) and the octopuses Hapalochlaena lunulata (Geffeney et al, 2019) and Hapalochlaena maculosa (Whitelaw et al, 2020), replacements were also not observed in the NaV1.4a Domain III of L. sceleratus.…”
Section: Ttx Resistance Of Scna4 Sodium Channelsupporting
confidence: 93%
“…Previously, these mutations for T. rubripes and T. nigroviridis had not been associated with TTX resistance ( Venkatesh et al, 2005 ; Soong and Venkatesh, 2006 ). At the last positions of Domain IV, there are also two replacements to His and Ser in H. lunulata ( Geffeney et al, 2019 ) and H. maculosa ( Whitelaw et al, 2020 ), which may inhibit TTX binding.…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequencing and RNA-Seq [32] Takifugu rubripes Involvement of the immune system in the liver. RT-PCR [33] Takifugu rubripes Involvement of the immune system in the liver.…”
Section: Rattus Norvegicus Cells (Oec)mentioning
confidence: 99%
“…Although the benefits of acquired genes and the utilization of existing or duplicated genes ( Kondrashov 2012 ; Qian and Zhang 2014 ) for novel traits have been well studied through comparative evolutionary genomics and transcriptomics ( Zhou et al 2019 ; Whitelaw et al 2020 ; Calla 2021 ), the benefits of gene losses are more difficult to verify. The study of convergent gene loss patterns may represent a first step in this direction, as such convergence provides insights into potential adaptive benefits of gene losses.…”
Section: Introductionmentioning
confidence: 99%